Maintaining Oxygenation Successfully with High Flow Nasal Cannula during Diagnostic Bronchoscopy on a Postoperative Lung Transplant Patient in the Intensive Care - Sara Diab; John F. Fraser (Case Reports in Critical Care)
Bronchoscopy is an important diagnostic and therapeutic intervention for a variety of patients displaying pulmonary pathology. The heterogeneity of the patients undergoing bronchoscopy affords a challenge for providing minimal and safe respiratory support during anesthesia. Currently, options are intubation and general anesthesia versus frequently inadequate sedation or local anaesthesia with low flow oxygen through nasal prongs or mouthpiece. The advent of high flow nasal cannula allows the clinician to have a “middle man” that allows high flow oxygen delivery as well as a degree of respiratory support, which in some cases has been noted to be between 3 and 4 cm of continuous positive airway pressure-like effect. There are minimal data analyzing the use of high flow nasal cannula during anesthesia for bronchoscopy. We present a case report of orthotropic lung transplant recipient undergoing diagnostic bronchoscopy whilst being supported with high flow nasal oxygen in the intensive care unit.